Minimally Invasive Laser Treatment of Ureterocele - Caione, Paolo; Gerocarni Nappo, Simona; Collura, Giuseppe; Matarazzo, Ennio; Bada, Maida; Del Prete, Laura; Innocenzi, Michele; Mele, Ermelinda; Capozza, Nicola (Frontiers in Pediatrics, 2019)
Introduction: Ureterocele may cause severe pyelo-ureteral obstruction with afebrile urinary tract infections in infants and children. Early decompressive treatment is advocated to reduce the risk of related renal and urinary tract damage. Endoscopic techniques of incision have been offered utilizing diathermic electrode. We adopted laser energy to release the obstruction of the ureterocele and reduce the need of further surgery. Our technique is described and results are presented, compared with a group of matched patients treated by diathermic energy. Materials and methods: Decompression was performed by endoscopic multiple punctures at the basis of the ureterocele. Holmium YAG Laser was utilized with 0.5-0.8 joule energy, through 8-9.8F cystoscope under general anesthesia. The control group received ureterocele incision by diathermic energy through pediatric resettoscope. Foley indwelling catheter was removed after 18-24 hours. Renal ultrasound was performed at 1,3,6 and 12 months follow-up. Voiding cysto-urethrogram and radionuclide renal scan were done at 6-18 months in selected cases. Statistical analysis was utilized for data evaluation. Results: From January 2012 to December 2017, 64 endoscopic procedures were performed: 49 were ectopic and 15 orthotopic ureteroceles. Fifty-three were in duplex systems, mostly ectopic. Mean age at endoscopy was 6.3 months (1-168). Immediate decompression of the ureterocele was obtained, but in 5 cases (8%) a second endoscopic puncture was necessary at 6-18 months follow-up for recurrent dilatation. Urinary tract infections and de novo refluxes occurred in 23.4% and 29.7% in the study group, compared to 36.9% and 43% in the controls (p<0.05). Further surgery was required in 12 patients (18%) at 1-5 years follow-up (10 in ectopic ureteroceles with duplex systems): 7 ureteral reimplantation for reflux, 5 laparoscopic hemy-nephro-ureterectomy for dysplastic hydronephrotic upper renal moiety. Secondary surgery was necessary in 39.4% of control group (p<0.05). Conclusions: Early endoscopic decompression should be considered first line treatment of obstructing ureterocele in infants and children. Multiple punctures at the basis of the ureterocele, performed by low laser energy, is resulted a really minimally invasive treatment, providing immediate decompression of the upper urinary tract and reducing the risk of further aggressive surgery.